PATHOGENETIC INTERACTION OF THYROID DISEASES AND GASTROINTESTINAL PATHOLOGY IN CHILDREN - Panoev Xurshid Shuxratovich (Scholar Express Journals, 2022)
The article summarizes current data on dysfunctional disorders of the gastrointestinal tract, liver and biliary tract in children with thyroid diseases. The course of diseases of the digestive system depends on the functional characteristics of the thyroid gland.
Keywords: Gastrointestinal Tract; Liver; Thyroid Gland; Children